2015
DOI: 10.1158/0008-5472.can-14-2498
|View full text |Cite
|
Sign up to set email alerts
|

IL6/JAK1/STAT3 Signaling Blockade in Endometrial Cancer Affects the ALDHhi/CD126+ Stem-like Component and Reduces Tumor Burden

Abstract: Cancer stem-like cells (CSC) may be critical to maintain the malignant behavior of solid and hematopoietic cancers. Recently, patients with endometrial cancer whose tumors expressed high levels of aldehyde dehydrogenase (ALDH), a detoxifying enzyme characteristic of many progenitor and stem cells, exhibited a relative reduction in survival compared with patients with low levels of ALDH. Given evidence of its role as a CSC marker, we hypothesized that high level of ALDH activity (ALDH hi ) in a tumor might posi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 42 publications
4
58
1
Order By: Relevance
“…In addition to its effect on androgen receptor signaling, IL6 is also important for the maintenance of stem cell properties in several cancers (5,(16)(17)(18), and blocking STAT3 activity has been shown to inhibit prostate cancer stem-like cells (5,16). Treatment of LNCaP with a combination of IL6 and enzalutamide led to a significant increase in stemness/self-renewal genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its effect on androgen receptor signaling, IL6 is also important for the maintenance of stem cell properties in several cancers (5,(16)(17)(18), and blocking STAT3 activity has been shown to inhibit prostate cancer stem-like cells (5,16). Treatment of LNCaP with a combination of IL6 and enzalutamide led to a significant increase in stemness/self-renewal genes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the IL6/JAK/STAT3 and AR signaling pathways, which are investigated in this study, are linked to prostate cancer progression and the development of castration resistance. In addition, several groups have demonstrated that activation of the IL6/JAK/STAT3 pathway is required for maintenance of stem cell properties in human malignancies (5,(16)(17)(18), whereas androgen receptor activity is known to induce differentiation and suppress self-renewal and proliferation of prostate cancer cells (19).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, tumor-associated inflammation factors within the tumor niche play a pivotal role in the maintenance of cancer cell stemness and the resultant tumor initiation/malignancy [6, 7]. However, tumor-associated inflammation genes or pathways that govern cancer cell stemness remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, antibodies that neutralize IL6 or block IL6 receptor (R) a are in clinical trials for ovarian, prostate, and renal cancers (7,8). In an orthotopic nude endometrial carcinoma model, IL6 promoted tumor growth (9), while targeted inhibition of the IL6 receptor dramatically reduced tumor growth in HEC1A cell-derived subcutaneous xenografts in immunodeficient mice (10).…”
Section: Introductionmentioning
confidence: 99%